Collegiate instructors’ perceptions and practices in integrating technology in Spanish language instruction - Barboza, Ana Lorena (Kansas State University, 2010)
Spanish instructors are not neo-phobic of instructional technology (IT), and they will affirm they are not afraid of IT just to avoid being labeled as ‘living dinosaurs.’ Most of them just do not have the know-how to explore and use IT in-depth. Regardless, they are more familiar with the diverse IT world available. In this study the main factors influencing Spanish language educators to use IT (or not) in their Second Language Acquisition (SLA) teaching methodology were discussed. Data from Spanish instructors in eight Kansas universities was analyzed to understand their perceptions and attitudes regarding the use of IT in their classrooms. Mixed methodologies were used: A quantitative survey targeting 80 instructors from the Modern Language Departments was developed. The survey had one section on demographic information and a second with 43 items dealing with perceptions related to IT. Afterwards, a case study with four in-depth interviews was conducted to elucidate richer descriptions and potentially corroborate patterns identified from the survey data. Data analysis revealed that most Spanish instructors have positive perceptions and attitudes towards IT. From the survey, nine themes emerged. Six of them formed a super-ordinate category showing that instructors consider IT useful for teaching culture in the target language, and in facilitating general knowledge. In this super-ordinate category, the six emergent themes are considered subordinate themes. The other three emergent themes formed another super-ordinate category with three subordinate themes: faculty require more time, training and technical resources to be able to integrate IT in their teaching. The four interviews explored what perceptions (or characteristics) stand out among faculty along a continuum of non-users to users with respect to the integration of IT; this allowed the researcher to confirm the instructors’ perceptions and attitudes on the nine emerging themes. Spanish instructors would integrate more modern tools in their teaching if they had more opportunities and support to be better informed; received appropriate training in their specific field; and were advised of available technology. As the findings showed, educators are no longer afraid of technology. Finally, conclusions of the findings were offered as well as recommendations for future research.
Keywords: Instructional information technology (IT); Perceptions and practices; College Spanish; Spanish language; Language instruction; Second Language Acquisition (SLA); Education, Curriculum and Instruction (0727); Education, Language and Literature (0279); Education, Technology (0710)